2021
DOI: 10.1007/s11926-021-01038-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Antiphospholipid Syndrome in the General Population

Abstract: Purpose of Review The epidemiology of antiphospholipid syndrome (APS) is poorly understood. Here, we review the current understanding of the epidemiology of antiphospholipid syndrome in the general population and the frequency of antiphospholipid antibodies in the general population in patients with obstetric morbidity, arterial events, and venous thromboembolism. Recent Findings There have been few population-based studies that estimated the prevalence and incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
54
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 59 publications
(50 reference statements)
2
54
0
3
Order By: Relevance
“…Although epidemiological data on APS remain limited, and the gender ratio varies widely across studies, ranging from 10:1 to 1:1 ( 24 ), in our study we found a female predominant ratio of approximately 3:1.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Although epidemiological data on APS remain limited, and the gender ratio varies widely across studies, ranging from 10:1 to 1:1 ( 24 ), in our study we found a female predominant ratio of approximately 3:1.…”
Section: Discussionsupporting
confidence: 41%
“…Although epidemiological data on APS remain limited, and the gender ratio varies widely across studies, ranging from 10:1 to 1:1 (24), in our study we found a female predominant ratio of approximately 3:1. The causes of this predominance are certainly multifactorial, mainly linked to the X chromosome and to different genes expressed exclusively on this chromosome, such as TLR7, FOX-P3, CD40L (25) and other genes involved in the process of immune response (26).…”
Section: Discussionsupporting
confidence: 41%
“…1 The incidence of APS is estimated to be 1-2 per 100 000 and the prevalence is about 40-50 cases per 100 000. 2 Antiphospholipid syndrome causes more than 20% of strokes in young patients. 2 Diagnostic criteria for APS include the persistent presence of antiphospholipid antibodies (lupus anticoagulant, anticardiolipin or aβ2GP1 antibodies) in association with thrombotic or obstetric complications (see revised Sapporo criteria, Box 1).…”
Section: Discussionmentioning
confidence: 99%
“…2 Antiphospholipid syndrome causes more than 20% of strokes in young patients. 2 Diagnostic criteria for APS include the persistent presence of antiphospholipid antibodies (lupus anticoagulant, anticardiolipin or aβ2GP1 antibodies) in association with thrombotic or obstetric complications (see revised Sapporo criteria, Box 1). 3 Antibodies may arise transiently from many factors, including concurrent illness, and therefore must be tested twice, at least 12 weeks apart.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with previous studies investigating DOAC removal ex vivo in patient samples, in which up to 25–97% of patients have positive LAC screening/test results during DOAC treatment [ 2 , 5 , 6 , 12 ]. This far exceeds the prevalence of phospholipid antibodies in the general population [ 13 ]. Timing of blood sampling affects the results, because samples drawn at peak drug levels (i.e., 2–3 h after dose) show more laboratory interference than trough-level (12–24 h) samples [ 7 ].…”
Section: Discussionmentioning
confidence: 99%